2008
DOI: 10.1002/anie.200802906
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Ultimate Size Limit of the Memory Effect in Spin‐Crossover Solids

Abstract: The phenomenon of spin crossover (SCO) between high-spin (HS) and low-spin (LS) states of 3d 4 -3d 7 transition-metal complexes has attracted much interest.[1] Although the origin of the spin-crossover phenomenon is purely molecular, the macroscopic behavior of these systems in the solid state is strongly influenced by short-and long-range interactions (of mainly elastic origin) between the transition-metal ions, giving rise to remarkable cooperative phenomena, such as first-order phase transitions.[2] One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(135 citation statements)
references
References 43 publications
5
130
0
Order By: Relevance
“…[10] To precisely control the particle size in this study, the reactant concentration was kept constant (0.05 ) and only the mass of the nonionic polyoxyethylenic surfactant Ifralan D0205 was varied (25, 78 and 85 %). In other reports of nanoparticle preparation, different sized particles were obtained through varying the solution metal concentration, [8,9] and we found that the strategy of keeping the concentration constant and varying the oil/water ratio allowed the size to be varied more precisely.…”
Section: Synthesis and Physical Characterizationmentioning
confidence: 89%
“…[10] To precisely control the particle size in this study, the reactant concentration was kept constant (0.05 ) and only the mass of the nonionic polyoxyethylenic surfactant Ifralan D0205 was varied (25, 78 and 85 %). In other reports of nanoparticle preparation, different sized particles were obtained through varying the solution metal concentration, [8,9] and we found that the strategy of keeping the concentration constant and varying the oil/water ratio allowed the size to be varied more precisely.…”
Section: Synthesis and Physical Characterizationmentioning
confidence: 89%
“…This is attributed to amorphisation and a reduction in the coherent domain length of individual particles, through increased defects and a more significant surface contribution. 11 Cooperativity can be assessed through evaluation of the abruptness of the SCO curve and hysteresis widths via magnetometry. 12 Previous studies on the effects of grinding SCO materials involved grinding solutionsynthesized molecular SCO materials for several hours.…”
Section: (F)mentioning
confidence: 99%
“…In all these studies, the research of the control of the thermal hysteresis loop, and particularly, the identification of the relevant physical parameters allowing monitoring the hysteresis width is a key point for the practical applications of these systems. The current work aims to address this problem on SC nanoparticles on which an extensive work was devoted this last decade, both from the chemical view point by synthesizing new core-shell systems [28][29][30] and from the theoretical side, in which some attempts to explain the interplay between the matrix and the SCO properties [31][32][33][34][35][36] have been developed. Mikolasek et al [37] has studied the influence of surface/interface on the lattice dynamic of SCO nanoparticules using a spring-ball model.…”
Section: I-introductionmentioning
confidence: 99%